BoALMT1, an Al-Induced Malate Transporter in Cabbage, Enhances Aluminum Tolerance in Arabidopsis thaliana - Zhang, Lei; Wu, Xin-Xin; Wang, Jinfang; Qi, Chuandong; Wang, Xiaoyun; Wang, Gongle; Li, Mingyue; Li, Xingsheng; Guo, Yang-Dong (Frontiers in Plant Science, 2018)
Aluminum (Al) is present in approximately 50% of the arable land worldwide and is regarded as the main limiting factor of crop yield on acidic soil. Al-induced root malate efflux plays an important role in the Al tolerance of plants. Here, the aluminum induced malate transporter BoALMT1 (KF322104) was cloned from cabbage (Brassica oleracea). BoALMT1 showed higher expression in roots than in shoots. The expression of BoALMT1 was specifically induced by Al treatment, but not the trivalent cations lanthanum (La), cadmium (Cd), zinc (Zn), or copper (Cu). Subcellular localization studies were performed in onion epidermal cells and revealed that BoALMT1 was localized at the plasma membrane. Scanning Ion-selective Electrode Technique was used to analyze H+ flux. Xenopus oocytes and Arabidopsis thaliana expressing BoALMT1 excreted more H+ under Al treatment. Overexpressing BoALMT1 in transgenic Arabidopsis resulted in enhanced Al tolerance and increased malate secretion. The results suggested that BoALMT1 functions as an Al-resistant gene and encodes a malate transporter. Expressing BoALMT1 in Xenopus oocytes or Arabidopsis thaliana indicated that BoALMT1 could increase malate secretion and H+ efflux to resist Al tolerance.